2023
DOI: 10.1186/s12954-023-00756-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences of methadone treatment changes during the first wave of COVID-19: a national community-driven survey

Abstract: Background During COVID-19, the Substance Abuse and Mental Health Services Administration (SAMHSA) allowed Methadone Maintenance Treatment (MMT) programs to relax in-person MMT requirements to reduce COVID-19 exposure. This study examines patient-reported changes to in-person methadone clinic attendance requirements during COVID-19. Methods From June 7, 2020, to July 15, 2020, a convenience sample of methadone patients (N = 392) were recruited in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…For example, a large survey conducted by Livingston et al among MOUD clinics in the Veteran Hospital Services showed that while methadone and buprenorphine delivery was affected, some patients tended to receive better coverage than others [ 32 ]. Another survey conducted with patients receiving take-home deliveries at SAMHSA during the pandemic found wide variability, with some patients receiving their at-home doses while others were still required to dose on site, increasing the risk of COVID-19 transmission [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a large survey conducted by Livingston et al among MOUD clinics in the Veteran Hospital Services showed that while methadone and buprenorphine delivery was affected, some patients tended to receive better coverage than others [ 32 ]. Another survey conducted with patients receiving take-home deliveries at SAMHSA during the pandemic found wide variability, with some patients receiving their at-home doses while others were still required to dose on site, increasing the risk of COVID-19 transmission [ 33 ].…”
Section: Discussionmentioning
confidence: 99%